Principals’ Learning Leadership and the Development of Learning Communities in Sekolah Penggerak of Aceh Tamiang - M Reza Pahlevi; Munawar Munawar; Siraj Siraj (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
The performance of teachers is a crucial factor influencing educational quality, especially in Indonesia, where both national and international evaluations reveal ongoing difficulties in student learning outcomes. This study is to investigate the impact of management competence, interpersonal communication, and success motivation on teacher performance in public elementary schools within the Meurah Dua Subdistrict. A quantitative descriptive methodology with a correlational survey design was implemented. The population comprised 128 teachers, all chosen using comprehensive sampling. Data were gathered using Likert-scale questionnaires that adhered to validity and reliability criteria (Cronbach’s ? > 0.70). Data were examined utilizing descriptive statistics, Pearson correlation, and multiple regression analysis. Anticipated outcomes suggest that management competence and achievement motivation significantly enhance teacher performance, whereas interpersonal communication has a good but comparatively weaker impact. All three variables are anticipated to strongly forecast teacher performance. The findings are expected to underscore the significance of leadership capacity and motivational techniques in enhancing instructional quality and teacher productivity.